RANCANG BANGUN SISTEM PEMANTAUAN LAHAN GAMBUT BERBASIS WIRELESS SENSOR NETWORK - Ery Murniyasih; Pujianti Wahyuningsih; Syarifah Fitrah Ramadhani (Electro Luceat, 2022)
The purpose of this research is to design a peatland monitoring system based on a data communication system between sensor nodes using Wireless Sensor Network (WSN) technology. Peatland is one part of the tropical forest ecosystem which is very vulnerable to fire disasters so it can cause harm to the community, both materially and non-materially. In this study, we will use the DHT11 sensor to detect the temperature and humidity of the environment and use the soil moisture sensor to read the temperature conditions of the peatlands. Next, we use NodeMCU ESP8266 to process the sensor data, then send it to the internet to be processed using Firebase services. Firebase is a platform made by Google that can display the results of sensor data processing in the online form using mobile applications and web services. The result of this research is that the WSN device that was built can provide information on the state of the temperature, humidity, and peat soil condition using the internet network so that the society can monitor the condition of the peatland by online using smartphone.